2001
DOI: 10.1095/biolreprod64.4.1273
|View full text |Cite
|
Sign up to set email alerts
|

Continuously Proliferative Stem Germ Cells Partially Repopulate the Aged, Atrophic Rat Testis after Gonadotropin-Releasing Hormone Agonist Therapy1

Abstract: Aging in the male human is accompanied by testicular atrophy, although relatively little is known about the mechanisms underlying germ cell loss. Testicular atrophy in the aged Brown Norway rat, an animal model for studies of aging in the human, has been attributed to a loss of spermatogonial stem cells. However, examination of testicular cross-sections from 27-mo-old Brown Norway rats indicated that approximately 14% of type A spermatogonia were stem cells. Furthermore, using bromodeoxyuridine labeling, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Rathi et al and Schoenfeld et al reported that testicular stem cells continuously proliferated in the aging testis after grafting3435. In the present study, we introduced a testis tissue grafting method for the enrichment of SSCs from adult testis connected with the simultaneous cultivation of these cells because tissue grafting is potentially be a better strategy for germ cell preservation and transplantation in humans than the cryptorchid or hyperthermia-exposed methods.…”
Section: Discussionmentioning
confidence: 87%
“…Rathi et al and Schoenfeld et al reported that testicular stem cells continuously proliferated in the aging testis after grafting3435. In the present study, we introduced a testis tissue grafting method for the enrichment of SSCs from adult testis connected with the simultaneous cultivation of these cells because tissue grafting is potentially be a better strategy for germ cell preservation and transplantation in humans than the cryptorchid or hyperthermia-exposed methods.…”
Section: Discussionmentioning
confidence: 87%
“…That study led to the conclusion that the inhibitory factor must be T or an androgenic metabolite of T. Other studies showed that suppression of androgens, using GnRH analogs, also stimulated spermatogonial differentiation in rats after spermatogenesis had been inhibited by procarbazine (6), hexanedione (37), heat treatment (38), or aging (39). GnRH-antagonist treatment also stimulated spermatogonial differentiation in juvenile spermatogonial depletion (jsd) mutant mice, which are depleted of all germ cells except A spermatogonia (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in testosterone may result from dysregulation at the hypothalamic-pituitary axis, in addition to age-related changes in Leydig cells. [17][18][19] Along with hormonal changes, alterations in testis vasculature may contribute to injury. In Sprague Dawley rats, aged testes have a significant reduction in blood vessel volume; 6-month and 24-month-old testes had 71% and 31% of the blood vessel volume, respectively, when compared to 3-month-old controls.…”
mentioning
confidence: 99%